IMPLEMENTASI NILAI-NILAI TASAWWUF BAGI SANTRI DALAM MENGHADAPI ERA GLOBALISASI DI PONDOK PESANTREN - Arifin, Zainul; Rusly, Fathullah; Islam, Saiful (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to examine the implementation of Sufi (Tasawuf) values among students (santri) at Pondok Pesantren Sirajut Thalibin, Racek, Tiris, Probolinggo, in facing the challenges of globalization. In an era marked by rapid technological advancement and shifting cultural values, santri are often exposed to influences that may distance them from spiritual and moral foundations. This research focuses on how the pesantren instills Tasawuf teachings—such as sincerity (ikhlas), patience (sabr), reliance on God (tawakkul), and modest living (zuhud)—to strengthen the students' spiritual resilience. The study uses a qualitative descriptive method through interviews, observation, and documentation. The findings reveal that through daily practices like dhikr, structured spiritual training, and the integration of Tasawuf into the curriculum and social life, students develop strong moral character and are better equipped to navigate the complexities of modern life without losing their spiritual identity. The conclusion emphasizes that the internalization of Tasawuf values plays a vital role in shaping santri who are morally grounded, spiritually aware, and socially responsible in the face of globalization.